The Relationship between Government and Private Consumption: A Replication Study of Fiorito and Kollintzas (European Economic Review, 2004) - Zhongchen Song (Journal of Comments and Replications in Economics (JCRE), 2022)
This paper replicates the article Fiorito and Kollintzas (2004) "Public goods, merit goods, and the relationship between private and government consumption". The authors investigated whether government consumption crowds out private consumption by splitting government consumption into two categories: Public goods and merit goods. The authors develop a model of household spending behaviour in the presence of government spending. They then estimate the model using difference GMM applied to 12 OECD countries between 1970 to 1996. This study re-estimated their main model specifications by attempting to re-construct their data. I also extended the data sample to a more recent period (1996 to 2015). My replication confirmed their finding that merit goods and private consumption are complements. On the other hand, I did not find support for their conclusion that public goods and private consumption are substitutes.
https://doi.org/10.15456/j1.2020282.083047
Keywords: E6; H3; C33; 330; Crowding Out Effect; Consumption; Replication Study